RADICAL ISLAMISM’S APPROACH TO THE KURDISH QUESTION IN TURKEY (1980-2002): “THE KURDISH QUESTION IS THE UMMAH'S QUESTION”* - Çelikçi, Abdül Samet (My University, 2021)
This study deals with how the Kurdish question was evaluated from a radical Islamist perspective and aims to reveal the approach adopted by radical Islamism in Turkey towards the Kurdish issue during the 1980s and 1990s. This study argues that there is a direct relationship between the ideas of radical Islamists in Turkey on the nation-state and nationalism, and the approach they adopt towards the Kurdish question, which is a national issue with an ethno-political content. Between 1980-2002, radical Islamism in Turkey, which was categorically opposed to the modern nationstate and nationalism, had adopted an overall ummah-centered and universalist political perspective and thus approached the Kurdish question from that standpoint as well. In this period, radical Islamism in Turkey has viewed the establishment of an independent Kurdish state to be a nationalist solution proposal and openly opposed it. Radical Islamism also has a clear position on the recognition of Kurdish identity and the socio-cultural rights of the Kurdish people. In thid context, radical Islamism argued that the state needed to recognize the Kurdish identity and grant the socio-cultural rights of the Kurdish people in the short run.